2019
DOI: 10.1111/1440-1630.12600
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of upper limb activity measures for 5‐ to 18‐year‐old children with bilateral cerebral palsy

Abstract: Aim To investigate measurement properties and feasibility of upper limb activity measures in children aged 5–18 years with bilateral cerebral palsy (CP). Methods Five electronic databases were searched to identify measures of upper limb activity with published psychometric data for children with bilateral CP aged 5–18 years. Measures included both Patient‐Reported Outcome Measures (PROMs) and observational measures. The COnsensus‐based Standards for selection of health Measurement Instruments checklist was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…6 A recent systematic review identified the BoHA as the only available observation-based instrument assessing bimanual performance in children with bilateral CP. 4 Very high interrater reliability has been reported for the BoHA, while test-retest reliability and responsiveness to change have not yet been established. 7 In addition to scale measurement properties and reliability indices, it is important to investigate the external validity of the BoHA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 A recent systematic review identified the BoHA as the only available observation-based instrument assessing bimanual performance in children with bilateral CP. 4 Very high interrater reliability has been reported for the BoHA, while test-retest reliability and responsiveness to change have not yet been established. 7 In addition to scale measurement properties and reliability indices, it is important to investigate the external validity of the BoHA.…”
Section: Discussionmentioning
confidence: 99%
“…3 One of the recommended outcome measures for evaluating hand function in children with bilateral CP is the newly developed Both Hands Assessment (BoHA). 4 The BoHA scale has been validated through Rasch analyses for children with bilateral CP classified in Manual Ability Classification System (MACS) levels I to III, aged between 18 months and 12 years. 5 The purpose of the BoHA is to measure and describe how effectively both hands are used in playful bimanual activities, as well as describing the degree of side difference between hands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACTIVLIM-CP is a questionnaire for parents that measures the performance of global activity in daily activities. It has been validated for children with CP ( 46 48 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bu nedenle, fonksiyonellikle ilgili değerlendirmeler genellikle iki üst ekstremiteyi içerir. 13 Bu yönden bakıldığında, El Becerileri Sınıflandırma Sistemi (EBSS) ve Elle İlgili Yetenek Ölçeği (EİYÖ-Çocuk) bilateral etkilenimi değerlendiren, hem SP'li çocuklarda hem de farklı popülasyonda sıklıkla kullanılan ölçekler olarak karşımıza çıkmaktadır. Fakat, EBSS'nin bir sınıflandırma aracı olması ve Türkçe geçerlik ve güvenirliği çalışılmış olan EİYÖ-Çocuk ölçeğinin bu amaçla kullanılan ve psikometrik olarak en objektif ölçüm yöntemi olduğu vurgulanmakla birlikte, EİYÖ-Çocuk ölçeğinin duyarlılığı konusunda da yeterli kanıtın olmadığı belirtilmektedir.…”
unclassified